2016
DOI: 10.1063/1.4965891
|View full text |Cite
|
Sign up to set email alerts
|

Magnon–phonon coupling and implications for charge-density wave states and superconductivity in cuprates

Abstract: The mechanism of high-temperature superconductivity of copper oxides (cuprates) remains unsolved puzzle in condensed matter physics. The cuprates represent extremely complicated system, showing fascinating variety of quantum phenomena and rich phase diagram as a function of doping. In the suggested "superconducting glue" mechanisms, phonon and spin excitations are invoked most frequently, and it appears that only spin excitations cover the energy scale required to justify very high transition temperature T c ~… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Increased pressure usually leads to broadening of electronic bands and eventually metallization because of increased orbital overlap induced by shorter interatomic distances . Pressure is also an important factor impacting the T c in oxygen-doped cuprates, which usually exhibit a maximum of T c in their phase diagram while at optimum external pressure. Similar effects might be envisaged for the doped AgF 2 . Because AgF 2 is known to undergo a drastic structural reorganization into a nanotubular polymorph at ca.…”
Section: Resultsmentioning
confidence: 90%
“…Increased pressure usually leads to broadening of electronic bands and eventually metallization because of increased orbital overlap induced by shorter interatomic distances . Pressure is also an important factor impacting the T c in oxygen-doped cuprates, which usually exhibit a maximum of T c in their phase diagram while at optimum external pressure. Similar effects might be envisaged for the doped AgF 2 . Because AgF 2 is known to undergo a drastic structural reorganization into a nanotubular polymorph at ca.…”
Section: Resultsmentioning
confidence: 90%
“…in establishing the J values for oxocuprates in both 1D [76] and 2D [77,78] systems. In early 2017, I have contacted José Lorenzana, excellent theoretical physicist of Argentinian origin working in Italy, and with his guidance, our experimental data collected by my hardworking PhD student, Jakub Gawraczyński, for 1D AgFBF 4 and for 2D AgF 2 , could finally be rationalized and will be published soon.…”
Section: From Large Covalence To Strong Magnetic Superexchangementioning
confidence: 99%
“…The effective HP dependence of T c reflects the combination of pressure-induced doping with other HP effects, on e.g. superexchange interactions, or oxygen ordering [20,21]. Given the competition between CDW and superconductivity in YBa 2 Cu 3 O 6+x , one might generally expect the CDW to be suppressed as T c increases under HP.…”
mentioning
confidence: 99%
“…Indeed, as in the case of light-induced transient superconductivity recently reported [33,34] and observed up to temperatures significantly larger than that of the CDW (which also rapidly disappears with the THz pumping [35]), this indicates that the details of the structural modifications under pressure, and of the subsequent changes in the microscopic interaction schemes between electrons might play a key role [36]. For instance, Raman scattering experi-ments have shown that the antiferromagnetic exchange interaction J, one of the candidates for the electronic pairing, increases under HP application [20,37,38]. It is also worth mentioning that according to earlier resistivity measurements the pseudogap and its onset temperature follow the increase of T c under HP, a result which was linked to a common intrinsic pressure dependence of superconductivity and the pseudogap [39,40].…”
mentioning
confidence: 99%